2017
DOI: 10.15578/jkn.v12i3.4212
|View full text |Cite
|
Sign up to set email alerts
|

Pendugaan Laju Sedimentasi Di Perairan Teluk Benoa - Bali Berdasarkan Citra Satelit

Abstract: Perairan Teluk Benoa Bali memiliki 6 sungai (tukad) yang bermuara pada perairannya. Tukad Mati dan Tukad Badung adalah 2 sungai terbesar pemberi pasokan sedimen. Pembangunan reklamasi di pelabuhan Benoa dan pembangunan Jalan Tol melintasi Teluk Benoa diduga meningkatkan sedimentasi. Tujuan penelitian ini adalah untuk mengetahui kejadian sedimentasi di perairan Teluk Benoa, dan memperoleh kisaran sedimentasi secara spasial yang terjadi dalam rentang 9 tahun terakhir. Analisis pendugaan sedimentasi dilakukan sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
6
0
3
Order By: Relevance
“…Based on the results of the respondents' discussion and literature review, the waters of Benoa Bay have indeed suffered damage and pollution since Serangan Island reclamation (1996), toll road construction, high load of pollutants entering the bay from inland waters due to tourism activities, port activities, and increased sedimentation [5][6][7][8]. The environmental conditions in Benoa Bay and the estimated impacts from the reclamation activities in the Benoa Bay are presented based on the physical, chemical and ecosystem aspects in Benoa Bay.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the respondents' discussion and literature review, the waters of Benoa Bay have indeed suffered damage and pollution since Serangan Island reclamation (1996), toll road construction, high load of pollutants entering the bay from inland waters due to tourism activities, port activities, and increased sedimentation [5][6][7][8]. The environmental conditions in Benoa Bay and the estimated impacts from the reclamation activities in the Benoa Bay are presented based on the physical, chemical and ecosystem aspects in Benoa Bay.…”
Section: Resultsmentioning
confidence: 99%
“…The data used in this research is primary data which includes data from direct measurements of sediment samples using sediment traps that have been installed around the location of the MV Boelongan Nederland shipwreck, and secondary data from several reports on government activities, and relevant journals. The sedimentation rate is the amount of sediment mass uplifted through one unit area each unit time [14][15][16]. The purpose of this research was to determine also to calculate the sedimentation rate, which is indicated to have a significant influence on the presence of the MV Boelongan Nederland shipwreck at seven (7) samples location.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the sedimentation rate was carried out based on data from sediment traps that had been installed at the location of the sinking ship and at the river mouth (table 1 and figure 1), where the sedimentation rate was the amount of sediment mass lifted through one unit area each unit time [15,20].According to Putra et al (2016) and Tanto et al (2017) [14,16] most marine sediments are material originating from land carried by rivers, where there are several types of sediment according to Hutabarat and Evans (2000) [21] in his book, which are divided by looking at where the source comes from, namely: 1) Lithogenous sediment, which are derived from the remains of rock erosion on land; 2) Biogenous sediment, which are sediments derived from skeletal remains of living organisms that can form deposits of fine particles commonly referred to as ooze and often settle in areas located far from the coast; and 3) Hydrogenous sediment, which are particles formed as a result of chemical reactions.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…3,0-4,9 5,0-5,9 6,0-6,9 >6,9 Tim ICCSR ( 2 0 1 0 ) Ketinggian muka laut (m) >30,0 20,1-30,0 10,1-20,0 5,1-10,1 (Handiani et al, 2017a). Perhitungan berbagai perubahan di pesisir dapat dibantu dengan analisis spasial hasil interpretasi citra Hasil analisis memberikan hasil cukup efektif, terutama untuk wilayah kajian yang luas (Tanto et al, 2017). Luas akresi dan erosi total di pesisir Kabupaten Subang dalam rentang tahun tersebut diestimasi dengan nilai relatif seimbang, yaitu…”
Section: Bahan Dan Metodeunclassified